2007
DOI: 10.1007/s10863-006-9063-9
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 in apoptosis, a novel therapeutic target

Abstract: During the past decade, extensive progress has been made toward understanding the molecular basis for the regulation of apoptosis. In mammalian cells undergoing apoptosis, two distinct mechanisms or pathways are operated and are triggered by cell death stimuli from intra-or extracellular environments, namely the intrinsic or extrinsic pathways, resulting in mitochondrial membrane depolarization. Several lines of evidence from our laboratories and others have indicated that galectin-3 plays an important role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 62 publications
5
94
1
2
Order By: Relevance
“…Galectin-3 (Gal-3), a member of the carbohydrate-binding protein family, contributes to neoplastic transformation, tumor survival, angiogenesis, and metastasis [3][4][5] . Gal-3 expression is associated with tumor invasion and metastasis in various human cancers, such as gastric, colon, prostate, pancreatic, and breast cancers [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Galectin-3 (Gal-3), a member of the carbohydrate-binding protein family, contributes to neoplastic transformation, tumor survival, angiogenesis, and metastasis [3][4][5] . Gal-3 expression is associated with tumor invasion and metastasis in various human cancers, such as gastric, colon, prostate, pancreatic, and breast cancers [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Galectin-3 binds to various antiapoptotic proteins such as Bcl-2, activated K-Ras, Alix/A1P1, and synexin to inhibit the intrinsic apoptotic pathways. The intracellular galectin-3 can also regulate extrinsic apoptotic pathways induced through death receptors such as Fas (CD95/apo-1), tumor necrosis factor receptor-1 (TNFR-1/p55/CD120), and TRAIL (TNF-related apoptosis inducing ligand/Apo2-L; Nangia-Makker et al 2007). This study revealed that luteal cells themselves were immunoreactive for galectin-3 in old CL formed at previous estrus cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3 expressed only at the villus tips may affect the shedding off and apoptosis of fully matured epithelial cells. In several in vitro studies, galectin-3 suppressed apoptosis by binding to various ligands such as Bcl-2 and Ras proteins (Nangia-Makker et al 2007). This study showed the diffuse localization of galectin-4/6 in the cytoplasm of immature enterocytes and a shift to the baso-lateral membrane in matured enterocytes, suggesting its involvement in membrane trafficking or stabilization.…”
Section: Discussionmentioning
confidence: 99%